RESISTÊNCIA GENÉTICA INDUZIDA EM PLANTAS CULTIVADAS - Carvalho, Nathália Leal (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2012)
http://dx.doi.org/10.5902/223611705930 Induction of resistance involves the activation of latent existing defense mechanisms in plants inresponse to treatment with biotic or abiotic agents. The plants have inducible defense system, inorder to save energy. Thus, induced resistance under natural conditions would cost only in thepresence of the pathogen. However, plants that invest their resources to defend themselves in theabsence of pathogens to bear costs that reflect the productivity, since the metabolic changes thatlead to adaptive resistance present cost associated, which can weigh more than the benefit. Thenegative effect on productivity is mainly chemical inducers which are used repeatedly or in higherdoses. Thus, in some cases can be walking on a narrow line between cost and benefit, where thecure can be as bad as the disease itself.